(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
Water-resources characteristics of Lake Sevan are closely connected with the development phases of problems of the Lake. In the article are give descriptions which have been obtained due to statistical analysis and summarization of annual water balance of the lake and other water-resources activities. In the article also are given results of water use of the lake, also description of general elements of water balance, evaporation, and natural runoff (active output) of the lake, which depends on changes of its morphometry.